Sire Effects on Post-Weaning Growth of Beef-Cross-Dairy Cattle: A Case Study in New Zealand - Natalia Martín; Nicola Schreurs; Stephen Morris; Nicolás López-Villalobos; Julie McDade; Rebecca Hickson (Animals, 2020)
Little is known about the growth performance of beef sires used over dairy cows in New Zealand. This experiment aimed to evaluate the growth of Angus and Hereford sires via progeny testing of beef-cross-dairy offspring born to dairy cows and grown on hill country pasture. Live weights at 131, 200, 400, 600 and 800 days were analysed from a dataset of 5208 records from 1101 progeny of 73 sires. The means of the progeny group means for live weight were 118.6 kg at 131 days, 159.1 kg at 200 days, 284.2 kg at 400 days, 427.0 kg at 600 days and 503.6 kg at 800 days, and the overall daily growth rate was 0.58 kg/day from 131 to 800 days. The sire affected (p < 0.05) the live weight of their progeny at all ages. Differences in live weights between the lightest and heaviest progeny group means increased from 19 kg at 131 days to 90 kg at 800 days. Even though growth of calves was likely restricted to 200 days, live weight at 200 days explained 51–56% of the variation in live weights at 400 and 600 days (p < 0.05). Thus, the use of beef sires selected for growth has the potential to increase the live weight of cattle born on dairy farms for meat production.